Impact of genotype, body weight and sex on the prenatal muscle transcriptome of Iberian pigs - García-Contreras, Consolación (PLoS One, 2020)
Growth is dependent on genotype and diet, even at early developmental stages. In this study, we investigated the effects of genotype, sex, and body weight on the fetal muscle transcriptome of purebred Iberian and crossbred Iberian x Large White pigs sharing the same uterine environment. RNA sequencing was performed on 16 purebred and crossbred fetuses with high body weight (340±14g and 415±14g, respectively) and 16 with low body weight (246±14g and 311±14g, respectively), on gestational day 77. Genotype had the greatest effect on gene expression, with 645 genes identified as differentially expressed (DE) between purebred and crossbred animals. Functional analysis showed differential regulation of pathways involved in energy and lipid metabolism, muscle development, and tissue disorders. In purebred animals, fetal body weight was associated with 35 DE genes involved in development, lipid metabolism and adipogenesis. In crossbred animals, fetal body weight was associated with 60 DE genes involved in muscle development, viability, and immunity. Interestingly, the results suggested an interaction genotype*weight for some DE genes. Fetal sex had only a modest effect on gene expression. This study allowed the identification of genes, metabolic pathways, biological functions and regulators related to fetal genotype, weight and sex, in animals sharing the same uterine environment. Our findings contribute to a better understanding of the molecular events that influence prenatal muscle development and highlight the complex interactions affecting transcriptional regulation during development.